Educational Unemployment Factory in 9 Cities of East Java Province - Ramadhan, Adeva Dimas; Primandhana, Wiwin Priana; Wardaya, Wirya (Journal of Community Service and Society Empowerment, 2024)
The problem of educated unemployment in 9 cities of East Java Province until 2023 is still quite high compared to uneducated unemployment. There are several factors that cause the high number of educated unemployed in 9 cities of East Java Province, namely, Industrial Sector Investment, Minimum Wage and Economic Growth. This study aims to determine the influence of independent variables on the dependent variable in 9 cities, East Java Province from 2013 to 2022. In this research, linear regression analysis uses panel data using quantitative methods and secondary data at BPS (Central Statistics Agency) of East Java Province in 2013 to 2022 and uses the fixed effect model (FEM) as the best model. The results obtained in this research show that investment in the industrial sector has a positive and significant influence on educated unemployment in East Java Province. Meanwhile, minimum wages and economic growth are known to have no effect on educated unemployment in East Java Province.